Green Analytical Approach for the Determination of Zinc in Pharmaceutical Product Using Natural Reagent - Hemraj Sharma; Arjun Sharma; Bimala Sharma; Sonu Karna (International Journal of Analytical Chemistry)
A selective, sensitive, and environmentally safe spectrophotometry method was developed and validated for the determination of zinc in pharmaceutical substances using natural reagents obtained from the leaves of plant Acacia catechu. Different factors were optimized such as volume of reagent, selection of pH, and stability of the color complex. The drug showed a stable yellowish orange color complex at 550 nm. The greenness of the methods was estimated using an eco-scale tool where the presented method was found to be excellent green with an ecoscore of 84 based on spectrophotometric determination. Also, the greenness of the method was assessed by the Green Analytical Procedure Index and found to be eco-friendly. The method was validated in conformance with ICH guidelines, with acceptable values for linearity, accuracy, precision, LOD, and LOQ. The linearity range for zinc sulphate was 5–25 μg mL−1 with an R2 value of 0.996. The % RSD for intraday precision and interday precision was less than 2%. The suggested method can be employed for the economic analysis of zinc in its pure form and various formulations. The presented spectrophotometric method is the first analytical method for the analysis of zinc present in zinc sulphate and showed greater ecoscale as compared to the official method.